Oxidative Annulation of Diphenylpropanamides via In Situ Hypervalent Iodine-Promoted Intramolecular C–N/C–O Bond Formation - Liang, Zhi-Peng; Yu, Ying-Xin; Sun, Yuan-Yuan; Wang, Yang; Wu, Zheng-Guang (SynOpen, 2021)
An aryl iodide catalyzed intramolecular oxidative transformation of diphenylpropanamide derivatives is described that can readily afford the C–N/C–O coupling products in a single step. The speed of the 1,3-aryl iodide migration process determines the diversity of target compound generation in this reaction. This straightforward approach can be performed with the use of inexpensive and readily available catalyst, transition-metal-free, mild conditions and good functional group tolerance.
Keywords: catalytic; aryl iodide; C–N bond formation; C–O bond formation